Molly's pilgrim - Cohen, Barbara; Duffy, Daniel M. (New York : Lothrop Lee & Shepard Books, 1998)
Told to make a Pilgrim doll for the Thanksgiving display at school, Molly is embarassed when her mother tries to help her out by creating a doll dressed as she herself was dressed before leaving Russia to seek religious freedom.
Keywords: Jews -- United States -- Juvenile fiction; Jews -- United States -- Fiction; Schools -- Fiction; Thanksgiving Day -- Fiction; Emigration and immigration -- Fiction; Russian Americans -- Fiction